The involvement of galectin-3 in skin injury in systemic lupus erythematosus patients. (April 2018) - Shi, Z; Meng, Z; Han, Y; Cao, C; Tan, G; Wang, L
Objective: Our previous research suggested that anti-galectin-3 antibody was highly associated with the development of lupus skin lesions in systemic lupus erythematosus (SLE). In this study we aimed to investigate the involvement of galectin-3 in SLE skin damage. Methods: The study consisted of 49 patients with SLE, 16 with dermatomyositis and 11 with systemic scleroderma and 20 healthy controls. Galectin-3 was examined by ELISA and immunohistochemical staining in serum and skin, respectively. Results: Serum galectin-3 was significantly higher in patients with SLE than in those with dermatomyositis ( P  < 0.01), systemic scleroderma ( P  < 0.001) and healthy controls ( P  < 0.001); however, it was comparable between SLE patients with and without skin lesions ( P  = 0.2010 and was not correlated with cutaneous disease activity ( r  = −0.020, P  = 0.93) or damage score ( r  = −0.380, P  = 0.09). Galectin-3 expression was reduced in epidermis in lesional skin from patients with SLE, dermatomyositis and systemic scleroderma compared to healthy controls ( P  = 0.0055), whereas it was comparable among diseases ( P  > 0.05). As for subtypes of skin lesions in SLE, galectin-3 expression was lower in chronic cutaneous lupus erythematosus than in acute cutaneous lupus erythematosus ( P  = 0.0439). Conclusion: Serum galectin-3 is unlikely to play a role in the pathogenesis of lupus skin damage, but can be a potential biomarker for the measurement of SLE disease activity. Galectin-3 is greatly reduced in patients with lupus lesions compared with healthy controls, which may contribute to the recruitment of inflammatory cells in the skin.